1980
DOI: 10.1063/1.440093
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of Mg porphin, Cu porphin, and Pd porphin luminescence

Abstract: Temperature, pressure, and size dependence of Pd-H interaction in size selected Pd-Ag and Pd-Cu alloy nanoparticles: In-situ X-ray diffraction studies Fluorescence spectra of MgP in triphenylene and phosphorescence spectra of CuP and PdP in triphenylene have been obtained from room temperature down to looK. Analysis of the temperature dependence of the MgP spectra shows that the coupling between the Mg porphin guest and the triphenylene host is weak. A temperature-dependent splitting of the 0--0 phosphorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
1

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 11 publications
4
8
1
Order By: Relevance
“…The matter is that the phosphorescence spectra of Cu porphyrins with a pronounced vibrational structure including the mentioned QLS of CuP phosphorescence [9,13] have been obtained so far for the cases when the lower levels 2 T 1 and 4 T 1 correspond to the electronic configuration 3 (1a 1u 4e g ) of the porphyrin ligand. Calculation [6,7] for this case yields DE DQ = 319 cm À1 , which agrees well with the given experimental values for CuP [9,10]. It is known from the theory of electronic spectra of porphyrins (see e.g.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The matter is that the phosphorescence spectra of Cu porphyrins with a pronounced vibrational structure including the mentioned QLS of CuP phosphorescence [9,13] have been obtained so far for the cases when the lower levels 2 T 1 and 4 T 1 correspond to the electronic configuration 3 (1a 1u 4e g ) of the porphyrin ligand. Calculation [6,7] for this case yields DE DQ = 319 cm À1 , which agrees well with the given experimental values for CuP [9,10]. It is known from the theory of electronic spectra of porphyrins (see e.g.…”
Section: Resultssupporting
confidence: 86%
“…Our data on CuTPrP can be commented on as follows. The preferred activity of two vibrations of frequencies of about 200 cm À1 agrees with the data for CuP [9,10]. The higher intensity of the 0-0 transition is possibly due to the more efficient spin-orbit interaction in the first order.…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, the luminescence emission at room temperature proceeds most likely via the 2 T→ 2 S 0 transition, where the tripdoublet state is reached via a thermal equilibrium, and its temperature dependence allows an estimation of the 2 T– 4 T separation. This was unambiguously shown for CuP by following the phosphorescence emission; a 267 cm –1 splitting was found there for the 2 T– 4 T splitting . The 2 S 0 → 2 T transition has a non-negligible oscillator strength, as measured through its absorption spectrum on the red edge of the 2 S 1 – 2 S 0 transition at ∼14700 cm –1 . , …”
Section: Discussionmentioning
confidence: 57%
“…This was unambiguously shown for CuP by following the phosphorescence emission; a 267 cm −1 splitting was found there for the 2 T− 4 T splitting. 32 The 2 S 0 → 2 T transition has a non-negligible oscillator strength, as measured through its absorption spectrum on the red edge of the 2 S 1 − 2 S 0 transition at ∼14700 cm −1 . 6,33 4.1.3.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these are out-ofplane modes of a2 u symmetry, of which the mode of the lowest frequency (γ 9 ) is the doming motion of the complex. Detailed fluorescence and optical studies on various metallo porphines were reported by Bohandy and coworkers in the late seventies [83][84][85]. Further investigations of the phosphorescence on PdP in a matrix were carried out by A.…”
Section: Spectroscopic and Physical Propertiesmentioning
confidence: 99%